Calibration of Aimsun roundabout model: Pedestrian and vehicles flow. Issue 1 (1st January 2019) - Garmei, Saeed; Kashi, Ehsan
Abstract: Nowadays, pedestrians play an effective role on roundabout capacity and urban intersection. In this study, the results of stimulation and collaboration of Aimsun software are studied. First, the volume of pedestrians and passing vehicles is evaluated. The results showed that the average speed of pedestrian was 4.25 km/h, and the reaction time from the default of 1.35 s changed to 0.9 s. Also, the comparison results of the two moods showed that the average speed in the calibrated state decreased by 48% and the delay time decreased by 5%. Therefore, if the calibration of pedestrian movement is measured accurately.